A Sentinel Serological Study in Selected Zoo Animals to Assess Early Detection of West Nile and Usutu Virus Circulation in Slovenia - Kvapil, Pavel; Račnik, Joško; Kastelic, Marjan; Bártová, Eva; Korva, Miša; Jelovšek, Mateja; Avšič-Županc, Tatjana (Viruses, 2021)
Monitoring infectious diseases is a crucial part of preventive veterinary medicine in zoological collections. This zoo environment contains a great variety of animal species that are in contact with wildlife species as a potential source of infectious diseases. Wild birds may be a source of West Nile virus (WNV) and Usutu (USUV) virus, which are both emerging pathogens of rising concern. The aim of this study was to use zoo animals as sentinels for the early detection of WNV and USUV in Slovenia. In total, 501 sera from 261 animals of 84 animal species (including birds, rodents, lagomorphs, carnivores, ungulates, reptiles, equids, and primates) collected for 17 years (2002-2018) were tested for antibodies to WNV and USUV. Antibodies to WNV were detected by indirect immunofluorescence tests in 16 (6.1%) of 261 animals representing 10 species, which were sampled prior to the first active cases of WNV described in 2018 in Slovenia in humans, a horse, and a hooded crow (Corvus cornix). Antibodies to USUV were detected in 14 out of 261 animals tested (5.4%) that were positive prior to the first positive cases of USUV infection in common blackbirds (Turdus merula) in Slovenia. The study illustrates the value of zoological collections as a predictor of future emerging diseases.
Keywords: biosurveillance; Slovinsko; Flavivirus Infections; Flavivirus; Antibodies, Neutralizing; zvířata v ZOO; West Nile Fever; West Nile virus; západonilská horečka; Female; neutralizující protilátky; virus západního Nilu; infekce viry z rodu Flavivirus; zvířata; infectious diseases; ženské pohlaví; Slovenia; Animals, Zoo; Male; zoo environment; protilátky virové; Antibodies, Viral; Animals; mužské pohlaví; Usutu virus epidemiology